Analysis of Green Supply Chain Management Risk Mitigation in the Fiber Optic Service Provider Industry PT Era Bangun Telecomindo (PT EBTEL) East Java Regional - Yulianto, Rusman; Handayani, Wiwik (Journal of Management and Administration Provision, 2025)
PT. Era Bangun Telecomindo Regional East Java (PT EBTEL JATIM) is a company dedicated to providing fiber optic cable network services starting from the installation of new networks, network repairs and network rejuvenation in East Java which experiences problems in waste management and the emergence of high project fines due to lack of knowledge of risk identification, risk mitigation and green supply chain management. The purpose of the research is to find out the risk mitigation analysis that occurs in implementing Green Supply Chain Management (GSCM). This study uses a quantitative descriptive approach with the House Of Risk (HOR) method to analyze the risks within the company's Supply Chain Operation Reference (SCOR) framework. Data collection through the interview and questionnaire process, and data processing uses formula functions in Microsoft Excel. The results of the study found that there is risk identification, risk assessment, and risk mitigation from the company's Green Supply Chain Management framework, which can reduce the cost of fines incurred by the company.